A new species of Amazonian bluntnose knifefish Brachyhypopomus (Gymnotiformes: Hypopomidae), with comments on its phylogenetic position. Issue 4 (19th May 2021) - Dutra, Guilherme Moreira; Peixoto, Luiz Antônio Wanderley; Ochoa, Luz Eneida; Ohara, Willian Massaharu; Santana, Carlos David de; Menezes, Naércio Aquino; Datovo, Aléssio
Abstract : A new species of the bluntnose knifefish genus Brachyhypopomus Mago-Leccia is described from headwaters of upper Rio Juruena, and upper Rio Machado, Amazon basin, Brazil. The new species differs from all congeners by the absence of a small independent ossification of the Weberian complex located posterodorsally to the supraoccipital. It can be additionally distinguished from its congeners by a set of characters in combination that includes: absence of accessory electric organ over the opercular region, absence of a prominent pale uninterrupted middorsal stripe on body, presence of scales on the entire middorsal region of body, dorsal rami of the recurrent branch of anterior lateral-line nerve not externally visible, presence of a dark suborbital stripe, and possession of 8–10 scale rows above the lateral line. The phylogenetic position of the new species is inferred by its inclusion in a total-evidence matrix with data from morphology, mitochondrial genes, and nuclear genes of all species. The new species is apparently restricted to upland tributaries of the Chapada dos Parecis, more than 500 m high. Comments on the occurrence of fish species in multiple independent basins at Chapada dos Parecis are also provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:620C58EB-4DA7-4322-9E2D-ACF4152DB0C7